Design and synthesis of a novel BODIPY-labeled PSMA inhibitor. Issue 3 (1st February 2020) - Son, Sang-Hyun; Kwon, Hongmok; Ahn, Hye-Hyun; Nam, Hwanhee; Kim, Kyul; Nam, SangJin; Choi, Doyoung; Ha, Hyunsoo; Minn, Il; Byun, Youngjoo
Graphical abstract: Abstract: Prostate-specific membrane antigen (PSMA) is a zinc-bound metalloprotease which is highly expressed in metastatic prostate cancer. It has been considered an excellent target protein for prostate cancer imaging and targeted therapy because it is a membrane protein and its active site is located in the extracellular region. We successfully synthesized and evaluated a novel PSMA ligand conjugated with BODIPY650/665 . Compound 1 showed strong PSMA-inhibitory activity and selective uptake into PSMA-expressing tumors. Compound 1 has the potential to be utilized as a near infrared (NIR) optical imaging probe targeting PSMA-expressing cancers.